A Meditation: Why Teach? - Joonna Smitherman Trapp (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
What makes teaching a vocation that continues to draw smart and talented people even though the pay can be less-than-great, the workload damaging, and the rewards from societal and political opinion currently nonexistent? Frederick Buechner, a presbyterian minister, talks about the notion of vocation in his well-known book, Wishful Thinking. Our English word “vocation” comes from vocare, a Latin word meaning “to call,” and Buechner further defines the word as signifying “the work” we are “called to do” (118). I’m always amazed at my university that teachers haven’t heard about this idea. To them, vocation smacks of career-mindedness and doesn’t fit very well with a liberal arts impulse.
Keywords: JAEPL